Zwischen Realität und Fantasiewelt: Die psychologischen Wirkungen immersiver Freizeitparkgestaltung auf Konsumentscheidungen - Jakob Schümann; Maria Weege (IU Internationale Hochschule, 2026)
– Amusement parks are more popular than ever in Germany, transporting their guests into artificial worlds that tell their own stories. Theming and storytelling are an integral part of the holistic experience in many parks and inevitably have an effect on visitors. Nevertheless, there is a lack of scientific understanding of the psychological effects triggered by immersive amusement park design and how it influences consumer behavior. This work therefore aims to explore the psychological effects of immersive amusement park design and its influence on the choice of the amusement park visited. To this end, 115 people who had visited at least one amusement park in the past three years were asked about their subjective feelings during their visit in an online survey. The research revealed that aesthetic amusement park design triggers positive emotions, which in turn appear to promote customer loyalty. The immersion experienced during the visit promotes flow states, can satisfy social needs and the need to escape from everyday life, and is a relevant decision-making criterion when choosing an amusement park. These findings can help amusement parks make strategic investment decisions and form the basis for further research in this field.
Keywords: M31; M37; 650; amusement park design; theming; immersion; emotion; flow; customer loyalty; consumer decisions